Effect of physiological and pharmacological stress on heart rate, blood pressure, and echocardiographic measurements in healthy Warmblood horses - Alexander Dufourni; Eva Buschmann; Ingrid Vernemmen; Glenn VanSteenkiste; Gunther vanLoon; Annelies Decloedt (Journal of Veterinary Internal Medicine, 2024)
Abstract Background Echocardiographic measurements are important prognostic indicators but might be influenced by heart rate and blood pressure. This is particularly important when comparing repeated examinations. Hypothesis To determine the effect of physiological stress at mildly increased heart rates and pharmacological challenge using IV administration of N‐butylscopolammonium bromide and metamizol sodium on heart rate, blood pressure, and echocardiographic measurements. Animals Twenty healthy Warmblood horses. Methods Randomized crossover study. Horses were examined echocardiographically by 2‐dimensional, M‐mode, pulsed wave (PW) Doppler, and PW tissue Doppler imaging with simultaneous ECG recording and noninvasive blood pressure measurements during rest, physiological stress, and pharmacological challenge. Cardiac dimensions and functions were measured by a blinded observer. Data were analyzed using repeated‐measures analysis of variance. Results Mean heart rate and arterial blood pressure were significantly higher during physiological stress (46 ± 2 bpm, 93 ± 16 mm Hg) and pharmacological challenge (62 ± 13 bpm, 107 ± 17 mm Hg) compared with rest (34 ± 3 bpm, 86 ± 12 mm Hg; P < .05). Compared with rest, physiological stress resulted in increased left atrial fractional area change (34.3 ± 7.5 vs 27.3 ± 5.1%; P = .01) and left ventricular late diastolic radial wall motion velocity (13 ± 3 vs 10 ± 2 cm/s; P = .01) but had no significant effect on most other echocardiographic variables. Compared with rest, pharmacological challenge led to significantly decreased left atrial and diastolic ventricular dimensions (left ventricular internal diameter: 10.3 ± 0.9 vs 10.7 ± 0.8 cm; P = .01), increased aortic and pulmonary diameters, and ventricular wall thickness. Conclusions and Clinical Importance Physiological stress at mildly increased heart rates significantly enhanced atrial pump function. Larger heart rate and blood pressure increases during pharmacological challenge resulted in altered cardiac dimensions. This should be taken into account when evaluating echocardiographic measurements at increased heart rates.